Application of the STEAM Approach in Physics Education in Indonesia: as an Initiative in Realizing the Sustainable Development Goals - Vika Luthfiyatun Ni'mah; Hanandita Veda Saphira (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: The research aims to study the implementation of the STEAM approach in learning physics in Indonesia. Method: The method applied is a library study or literature review. This involves analyzing articles related to the STEAM approach in physics education in Indonesia, specifically those published between 2019 and 2023. Results: Findings reveal that the application of the STEAM approach in learning physics in Indonesia is relatively low during this period. Teachers encounter considerable challenges in effectively applying this approach. However, there are instances of successful research that demonstrate the effective use of the STEAM method to achieve desirable educational outcomes. Novelty: The research offers valuable new insights into the application of the STEAM approach in physics learning in Indonesia and connects these insights to the larger initiative of achieving the Sustainable Development Goals (SDGs). Future studies could investigate the relationship between the implementation of the STEAM approach in physics education and the progress towards achieving SDG goals through various educational initiatives. This exploration could help identify effective strategies for integrating STEAM principles into physics education and further contribute to sustainable development in the region.